PLANNING AND DESIGN COHOUSING FACILITIES WITH NATURE IN DENPASAR: Bahasa Indonesia - Sastra, I Made Windhu Langun; Putra, Ida Bagus Gede Parama; Darmawan, I Gede Surya; Arthana, I Nyoman Nuri; Nugraha , Putu Gede Wahyu Satya (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Millennials in Bali are facing difficulties in home ownership, with around 30% of the population without a place to live. To meet the need for housing that supports open social life, the development of Co-housing in Denpasar is important. Co-housing is designed to provide shared spaces that maintain the privacy of residents while facilitating social interaction. However, co-housing designs face issues such as space constraints, privacy, and cultural integration. Ensuring compliance with environmental regulations is also a challenge. The design process uses a combined approach of Research Method and Design Method, focusing on maximizing minimal space and utilizing connecting elements. The use of green concrete is expected to reduce CO2 emissions and create a comfortable environment for residents. Co-housing is expected to be a sustainable solution to Bali's housing needs.